Characterization of road traffic externalities in an intercity corridor - Sampaio, Carlos (2019)
This paperaims at evaluating road transportexternalities in anintercity corridor taking intoaccount the energetic and economic characterizationof the available road transport modes: Intercity Bus, Individual Transport and Shared Mobility.One of the purposesofthis analysis is to identify the External Costs (EC) and Private Costs (PC) of each mode/route and to which extent the best environmental option can be also considered as the best economical option. Results show the Intercity Bus at full or half occupancyis the best option in terms of EC, followed by the shared mobility. Regardingthe PC, results suggest that the best option is the shared mobility along route1 (motorway), followed by the intercity bus. When comparing both routes, route 1 has less PC thanroute 2 (national road). In order to reduce the overall environmental impacts of a transportsystem,one solution might bethe reduction of the EC through an optimization of the PC, ensuringthat the option with less EC is also the option with less PC,so that it can encourage users to choose routes and transport modes with lessenvironmental impacts.